Interactive strategies in the understanding of philosophical readings of the Ayacucho university students - Quispe Arroyo, Adolfo (2020)
The present research work was carried out with the objective of determining the influence of interactive strategies on the understanding of philosophical readings of university students from San Cristóbal de Huamanga, Ayacucho. To this end, we are guided by the positivist paradigm and its quantitative approach in quasi-experimental design. The study area was made up of university students. The sample consisted of 30 students from the Professional School of Obstetrics that made up the experimental group and 30 students from the Professional School of Nursing that made up the control group, both groups from the Faculty of Health Sciences. To compare the qualifications of the groups, a comprehension test of philosophical readings was applied. To test the hypothesis, the Wilcoxon statistical test was used. The results of the investigation determined that 70.0% of the students in the experimental group, with the application of interactive strategies, were within the good average and 30.0% were within the excellent average compared to the control group that did not reach these averages. . In conclusion, with a confidence level of 95% and a significance level of 5%, when obtaining a p value <0.05 (0.000), it is stated that the application of interactive strategies significantly influence the understanding of philosophical readings of the University students from the National University of San Cristóbal de Huamanga, Ayacucho-Peru.